Influence of placental exosomes from early onset preeclampsia women umbilical cord plasma on human umbilical vein endothelial cells - Gu, Mengqi; Zhang, Fengyuan; Jiang, Xiaotong; Chen, Pengzheng; Wan, Shuting; Lv, Qingfeng; Lu, Yuan; Zhou, Qian; Wang, Yanyun; Li, Lei (Frontiers in Cardiovascular Medicine, 2022)
Abstract: Early Onset Preeclampsia (EOSP, PE), is a multisystem disorder, that is characterized by hypertension, proteinuria and endothelial dysfunction. It may also increase the risk of cardiovascular diseases in offspring through “foetal origin of adult diseases”. Endothelial dysfunction is crucial for the occurrence and progression of cardiovascular diseases. Exosomes are extracellular vesicles that are involved in cell-to-cell communication and can regulate the barrier function of endothelial cells. In this study, we hypothesized that placenta-associated umbilical cord plasma-derived exosomes from Early Onset Preeclampsia women (PE-exo) impair vessel development by regulating endothelial cells. Oxidative stress-induced trophoblast dysfunction is a major pathology in PE. Therefore, We first constructed a hypoxia/reoxygenation (HR) model in HTR-8/Svneo cells to simulate the preeclampsia model of oxidative stress in vitro. Conditioned media was collected, and exosomes (Non-treated, NO-exo) and hypoxia/reoxygenation (HR-exo) were isolated by differential and buoyant density centrifugation. Next, umbilical cord plasma samples from women with normal pregnancies and matched early onset preeclampsia patients were used to isolate placental exosomes (N-exo and PE-exo, respectively). Then, we conducted a series of functional experiments. We showed that HR-exo and PE-exo impaired angiogenesis in HUVECs. Thus, we proposed that PE-exo disrupted normal function in vascular endothelial cells, which may result in vascular disorders in the offspring.